SUBSTANTIATION OF STRUCTURAL AND MECHANICAL CHARACTERISTICS OF BAKING BAKERY PRODUCTS - Fedoriv, Viktor; Liukhovets, Volodymyr; Lisevych, Dmytro; Manita, Ivan (SWorld-Ger Conference proceedings, 2024)
The article discusses the problems of bread baking. The oven is the leading place for baking bakery products. This is due to the fact that the entire complex of processes related to bread production is completed in the oven units. Oven performance is asse